The Effect of (MetCon) Training to Developing the Velocity Power and Defensive Follow-Up for Young Basketball Players - Ahmed Ishhab Abdulhussein; Jamal Sabri Faraj Al Abdullha (Institute of Medico-legal Publications Pvt Ltd, 2021)
The researchers decided to go into this study by applying a training method represented by (MetCon)training for the purpose of giving a clear and accurate scientific indication for coaches to develop theseabilities because their development will contribute to reaching high skill performance through upgradingthe physical capabilities and skill in defensive performance required to perform during play. The researchaims to prepare (MetCon) exercises to develop rapid strength and defensive follow-up for young basketballplayers. And learn about the impact of MetCon training in developing rapid strength and defensive followupfor young basketball players. The researchers hypothesized that there is a positive effect of (MetCon)training in developing rapid force and defensive follow-up for young basketball players. The researcher usedthe experimental method in the method of (equal control and experimental groups) of pre and post-test forits suitability to the nature of the research, and the research community was determined by the young Hillaclub basketball players for the year (2019-2020), whose number is (16) players. The research sample wasrepresented by (12) players who were deliberately selected from the research community and distributedrandomly into two groups, a control group and a group of MetCon training, and the most important conclusionwas that the MetCon training has a positive effect in developing rapid strength and defensive follow-up foryoung basketball players.